Best practice for the pharmacological management of hyperthyroid cats with antithyroid drugs. (27th December 2013) - Daminet, S.; Kooistra, H. S.; Fracassi, F.; Graham, P. A.; Hibbert, A.; Lloret, A.; Mooney, C. T.; Neiger, R.; Rosenberg, D.; Syme, H. M.; Villard, I.; Williams, G.
<x xml:space="preserve">Abstract</x> Pharmacological management of feline hyperthyroidism offers a practical treatment option for many hyperthyroid cats. Two drugs have been licensed for cats in the last decade: methimazole and its pro‐drug carbimazole. On the basis of current evidence and available tablet sizes, starting doses of 2·5 mg methimazole twice a day and 10 to 15 mg once a day for the sustained release formulation of carbimazole are recommended. These doses should then be titrated to effect in order to obtain circulating total thyroxine (TT4) concentrations in the lower half of the reference interval. Treated cases should be monitored for side‐effects, especially during the first months of treatment. Some side‐effects may require discontinuation of treatment. At each monitoring visit, clinical condition and quality of life should also be evaluated, with special attention to possible development of azotaemia, hypertension and iatrogenic hypothyroidism. When euthyroidism has been achieved, monitoring visits are recommended after 1 month, 3 months and biannually thereafter. Cats with pre‐existing azotaemia have shorter survival times. However, development of mild azotaemia during the initial course of treatment, unless associated with hypothyroidism, does not appear to decrease survival time. The long‐term effects of chronic medical management require further study.